Design and Implementation of a Renewable Energy System for Wind Turbine Power Analysis at Ikot Akpaden Community - Nkan, Imo Edwin; Etukudo, Aniekeme Hanson; Peter, Akoh Emmanuel (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Renewable energy plays a crucial role in sustainable development by enhancing human development and economic productivity. Analyzing the pipeline of installed wind farms across Africa reveals that the continent has substantial wind resources, with the potential to expand capacity by over 900% through the addition of 140 planned projects. The design and implementation of a renewable energy system for wind turbine power analysis in Ikot Akpaden Community serve as a valuable demonstration of wind energy’s effectiveness in mitigating high carbon flaring and other environmental pollutants, benefiting both the present and future environment. The analysis evaluates wind velocity and its significant power output based on the design parameters of the system in used. The experiment is carried out between the hours of 8:00 am to 9:00 pm for 7 days. Results show that wind velocity of Akpaden community varies between 2.67 m/s to 4.57 m/s with an average wind velocity of 4.03 m/s, there are limitation of some hours of the day without significant wind velocity but there is no complete 24 hours of a day that could be without free flow of wind energy. Using a wind turbine with a minimum sweep area of 0.283 m2, the power output produced by the available wind velocity ranges from 3.0 W to 8.82 W in a second, therefore by comparison with the theoretical power output of 11.32 W using the system designed parameters, there is 78 percent efficiency in the system design. Also, there is significant drop in power output between the hours of 3:00 pm and 4:00 pm as it is shown on the graphical representation which is as a result of decrease in the wind velocity of the area within that time. It is therefore seen that there is a useful power available in the wind velocity of the study region in which when it is collected and stored, can serve as a useful energy for student during their experiment and research purpose. The wind turbine’s output power can be improved to a desired percent using turbine with larger blade radius and sweep area.